The appointment process of independent directors in Malaysian listed companies - Abdullah, Shamsul Nahar; Zainal Abidin, Nor Hafizah; Abu Bakar, Intan Suryani; Ur Rahman, Anis (Virtus Interpress, 2016)
This study examines the appointment process for independent directors in public listed companies (PLCs) in Malaysia. To this end, open-ended interviews were conducted with chairmen of nomination committees of PLCs in Malaysia in order to understand the appointment process. The results revealed that nominations may come from various sources, including from the firm’s board members, CEO or owners. It was also found that the nominees are those within the personal network of the board members, CEO or owners. The main reason given was to shorten the appointment process and also because they knew the candidates personally. In terms of the selection criteria, the personal qualities of a candidate were found to be very important. In particular, the board puts emphasis on experience, expertise, professional qualifications, and reputation to identify a candidate who can commit to their tasks. However, the board does not consider race, religion, and gender as important selection criteria. Our findings reveal that it is the board that makes the final decision on the appointment or reappointment of independent directors. Based on our findings, we conclude that nominations for independent directorships mainly come from inside the firms and those nominated are within their networks. In other words, the independent directors are known or connected either to the board members, CEO or major shareholders. Hence, it would be very difficult for independent directors to perform a monitoring role as prescribed in agency theory. Rather, the independent directors are appointed to the board primarily to play a service role, consistent with resource dependency theory. The fact that firms prefer professionals with experience indicates that candidates for independent directorships are appointed because of their expertise and their service role.